Analysis of immunophenotypic methods in early diagnosis of acute leukemias (Research, Society and Development, 2020)
Objective: To highlight the importance of using immunophenotyping in the early diagnosis of acute leukemias. Methodology: This is an integrative literature review, using 12 articles published between 2016 and 2020. The language of the referenced articles was English and French, collected from Scielo, LILACS, BVS and EBSCO. Using the advanced search for the following keywords: Immunophenotyping, Acute Leukemia, Flow cytometry. Results: The articles used were published in the years 2016 and 2020. The articles demonstrated that the use of immunophenotyping, specifically flow cytometry, is an extremely important method for the diagnosis of acute leukemias. Markers used in each type and subtype of leukemia were identified, thus showing the peculiarity of the disease. Conclusion: The use of immunophenotypic methods with routine examinations contributes to the early diagnosis of patients with acute leukemia, making the treatment also be done early, thus increasing the survival of these individuals. According to the studies analyzed, immunophenotyping is constantly evolving and promises to simplify the process of diagnosis of various types of leukemia.